2021
DOI: 10.3390/biomedicines9101395
|View full text |Cite
|
Sign up to set email alerts
|

Protein Unfolding: Denaturant vs. Force

Abstract: While protein refolding has been studied for over 50 years since the pioneering work of Christian Anfinsen, there have been a limited number of studies correlating results between chemical, thermal, and mechanical unfolding. The limited knowledge of the relationship between these processes makes it challenging to compare results between studies if different refolding methods were applied. Our current work compares the energetic barriers and folding rates derived from chemical, thermal, and mechanical experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 75 publications
(134 reference statements)
0
3
0
Order By: Relevance
“…This strategy can principally be used also to conduct various other operations such as physical soundness (e.g., mass conservation), whether a result satisfies one or more principles or a partial differential equation, or constraints or design objectives. The use of natural language, combined with the capabilities of LLMs to effectively deal with numbers, data, code, and its execution, offers a wide array of possibilities in materials science and engineering and beyond, including, but not limited to, interpretability and the possibility of direct engagement with a human expert. , …”
Section: Discussionmentioning
confidence: 99%
“…This strategy can principally be used also to conduct various other operations such as physical soundness (e.g., mass conservation), whether a result satisfies one or more principles or a partial differential equation, or constraints or design objectives. The use of natural language, combined with the capabilities of LLMs to effectively deal with numbers, data, code, and its execution, offers a wide array of possibilities in materials science and engineering and beyond, including, but not limited to, interpretability and the possibility of direct engagement with a human expert. , …”
Section: Discussionmentioning
confidence: 99%
“…Mechanical methods measure the force that must be exerted on a domain to cause unfolding; single‐molecule atomic force microscopy (AFM) (Anderson et al, 2013; Zuo et al, 2021) has been used to probe the destabilization of domains by missense variants. While protein denaturation methods and protocols vary widely, experiments using chemical, thermal, and mechanical methods on titin domain Ig86 have demonstrated that the unfolding rates were consistent (Kelly & Gage, 2021). Thus, comparison across different methods is possible; however, re‐folding rates differ slightly.…”
Section: Prioritization Of Variantsmentioning
confidence: 99%
“…An even more detailed understanding of protein denaturation behavior can be achieved by contrasting the combination of chemical and thermal denaturation experiments ( 25 ) with the behavior of protein denaturation under force ( 26 ). Both types of experiment have been shown to produce similar denaturation pathways and rates ( 27 , 28 ). Computational simulations can add atomistic details ( 29 ) when combined with chemical/thermal denaturation studies.…”
Section: Introductionmentioning
confidence: 99%